2014
DOI: 10.3109/10717544.2014.903580
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of iRGD-modified liposomes with improved chemotherapeutic efficacy on B16 melanoma

Abstract: (2015) A comprehensive study of iRGD-modified liposomes with improved chemotherapeutic efficacy on B16 melanoma, Drug Delivery, 22:1, 10-20, DOI: 10.3109/10717544.2014 Here, iRGD-modified and doxorubicin-loaded sterically stabilized liposomes (iRGD-SSL-DOX) and passive liposomes (SSL-DOX) were prepared. A series of experiments were performed to evaluate the tissue penetration, cell penetration, tumor blood vessel damage and anti-tumor effect. The results of flow cytometry and confocal microscopy studies showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 45 publications
3
21
0
Order By: Relevance
“…12 The graing of Affitins on the LNC surface, a small articial model binding protein, modied the behavior of LNCs as already observed for nanomedicines modied with peptides. 41,44 As a rst step toward active targeting with LNCs, we wanted to study if an Affitin model, i.e. without any affinity for a melanoma biomarker, had intrinsic properties compatible with our goals.…”
Section: Discussionmentioning
confidence: 99%
“…12 The graing of Affitins on the LNC surface, a small articial model binding protein, modied the behavior of LNCs as already observed for nanomedicines modied with peptides. 41,44 As a rst step toward active targeting with LNCs, we wanted to study if an Affitin model, i.e. without any affinity for a melanoma biomarker, had intrinsic properties compatible with our goals.…”
Section: Discussionmentioning
confidence: 99%
“…first reported the C-end rule peptide (iRGD), and demonstrated that the peptide possesses the activity of NRP-1-dependent cell, vascular, and tissue penetration [32]. Subsequent reports showed that iRGD could enhance the intratumoral dissemination and antitumor efficacy of Doxorubicin [33–35], Paclitaxel [36, 37] and Endostatin [38] by conjugating with these drugs or drug-loaded vehicles in animal experiments. The other reports demonstrated that iRGD also could enhance the intratumoral accumulation and antitumor efficacy of Paclitaxel, Doxorubicin, Transtuzumab [24, 39], Cisplatin [40], by co-administration with these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor inhibition efficiency of FA-ETPNLCs, ETP-NLCs and was 88%, 77% and 38%, respectively. Better tumor inhibition efficiency indicates that FA-ETPNLCs showed better antitumor activity than ETP-NLCs and ETP solution for the treatment of gastric cancer in vivo (Dai et al, 2015). Obviously, decreased body weights, reduced foods intake and inactive moving behavior were found in ETP solution, blank NLCs and saline control groups.…”
Section: In Vivo Tissues Distribution and Antitumor Efficacymentioning
confidence: 93%